2021
DOI: 10.1507/endocrj.ej20-0502
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of solute carrier family 26 member 7 (Slc26a7) by thyroid stimulating hormone in thyrocytes

Abstract: Iodine transportation is an important step in thyroid hormone biosynthesis. Uptake of iodine into the thyroid follicle is mediated mainly by the basolateral sodium-iodide symporter (NIS or solute carrier family 5 member 5: SLC5A5), and iodine efflux across the apical membrane into the follicular lumen is mediated by pendrin (SLC26A4). In addition to these transporters, SLC26A7, which has recently been identified as a causative gene for congenital hypothyroidism, was found to encode a novel apical iodine transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…Recently, we evaluated the role of TSH on SLC26A7 expression using rat thyroid FRTL-5 cells and showed that TSH significantly suppressed SLC26A7 mRNA and protein expression. Although suppression of SLC26A7 is thought to result in decreased iodide transport activity, we additionally demonstrated that TSH induces localization of SLC26A7 to the plasma membrane, where it functions as a transporter [12].…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Recently, we evaluated the role of TSH on SLC26A7 expression using rat thyroid FRTL-5 cells and showed that TSH significantly suppressed SLC26A7 mRNA and protein expression. Although suppression of SLC26A7 is thought to result in decreased iodide transport activity, we additionally demonstrated that TSH induces localization of SLC26A7 to the plasma membrane, where it functions as a transporter [12].…”
mentioning
confidence: 51%
“…Total RNA was purified using the RNeasy Plus Mini Kit (Qiagen, Hilden, Germany). cDNA was synthesized using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Waltham, MA, USA) as described previously [12,22]; briefly, 1 μg total RNA was incubated with a mixture of 2 μL 10× RT buffer, 2 μL 10× RT Random Primers, 1 μL MultiScribe TM Reverse Transcriptase (50 U/μL), and 0.8 μL 25× dNTPs for 10 min at 25°C, 120 min at 37°C, and 5 min at 85°C. Real-time PCR was performed using Fast SYBR Green Master Mix (Applied Biosystems) and run on the Thermal Cycler Dice Real Time System III (Takara Bio, Tokyo, Japan) for 30 sec at 95°C, followed by 40 cycles of 5 sec at 95°C and 60 sec at 60°C, and then 1 cycle of 15 sec at 95°C, 30 sec at 60°C, and 15 sec at 95°C for dissociation.…”
Section: Total Rna Purification and Reverse Transcription Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetically ancient SLC26 gene family encodes multifunctional anion exchangers and anion channels transporting a broad range of substrates, including Cl - , HCO 3- , sulfate, oxalate, I − , and formate. It has been reported that SLC 26 member 7 (SLC26A7) was identified as a chloride–bicarbonate anion exchanger and/or as a Cl - channel in the kidney and stomach [ 34 , 35 ], whose gene mutations cause congenital deafness and dyshormonogenic goiter [ 36 ]. Alterations in Cl - channels can affect intracellular water content, vascular tone and arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%